Molecular characterization and functional expression of the Apis mellifera voltage-dependent Ca2+ channels. (March 2015) - Cens, Thierry; Rousset, Matthieu; Collet, Claude; Charreton, Mercedes; Garnery, Lionel; Le Conte, Yves; Chahine, Mohamed; Sandoz, Jean-Christophe; Charnet, Pierre
Abstract: Voltage-gated Ca 2+ channels allow the influx of Ca 2+ ions from the extracellular space upon membrane depolarization and thus serve as a transducer between membrane potential and cellular events initiated by Ca 2+ transients. Most insects are predicted to possess three genes encoding Cavα, the main subunit of Ca 2+ channels, and several genes encoding the two auxiliary subunits, Cavβ and Cavα2δ; however very few of these genes have been cloned so far. Here, we cloned three full-length cDNAs encoding the three Cavα subunits (AmelCav1a, AmelCav2a and AmelCav3a), a cDNA encoding a novel variant of the Cavβ subunit (AmelCavβc), and three full-length cDNAs encoding three Cavα2δ subunits (AmelCavα2δ1 to 3) of the honeybee Apis mellifera . We identified several alternative or mutually exclusive exons in the sequence of the AmelCav2 and AmelCav3 genes. Moreover, we detected a stretch of glutamine residues in the C-terminus of the AmelCav1 subunit that is reminiscent of the motif found in the human Cav2.1 subunit of patients with Spinocerebellar Ataxia type 6. All these subunits contain structural domains that have been identified as functionally important in their mammalian homologues. For the first time, we could express three insect Cavα subunits in Xenopus oocytes and we show that AmelCav1a, 2a and 3a form Ca 2+ channels with distinctive properties. Notably, the co-expression of AmelCav1a or AmelCav2a with AmelCavβc and AmCavα2δ1 produces High Voltage-Activated Ca 2+ channels. On the other hand, expression of AmelCav3a alone leads to Low Voltage-Activated Ca 2+ channels. Graphical abstract: Highlights: Honeybee genome contains seven genes encoding Ca 2+ channel subunits; three Cavα, one Cavβ and three Cavα2δ. We have cloned a full-length cDNA for all of these subunits and several alternative or mutually exclusive exons. These subunits contain protein domains shown to be functionally important in mammals. Functional expression of these subunits in Xenopus oocytes produces Ca 2+ channels with distinctive properties.